The Analysis of Code Switching Found In the Novel “Critical Eleven” - Anggarukma K D, A.A. Tri; Winaya, I Made (Humanis; Vol 23 No 1 (2019), 2019)
This paper is entitled “The Analysis Code Switching Found in The Novel “Critical Eleven”. The aims of this study  are to describe the types, function and to the analyse reasons of code switching used by the novelist. The data  in this study were taken from all chapters of the novel entitled “Critical Eleven”by Ika Natassa. Firstly , the code switching that occurs in novel were identified and then they were classified and analyzed based on their types, function, and reasons of code switching. The collected data were analyzed  using three theories ;  first the theory by Poplack as the main theor y used in this study ; this theory was used to analyze the three types of code swtching, the y are: Tag Switching, Inter-Sentental Switching, Intra-Sentential Switching. The second theory proposed by Apple and Muyken was used to anlyze the function of code switching. T hey divided the function s into six categories, which are: Referential Function, Directive Function, Expressive Function, Phatic Function, Metalinguistic Function, Poetic Function. The theory proposed by Grosjean was used to analyze the reason of code switching.  T here are ten reason s of code switching ; they are: To Fill A Linguistic Need For Lexical Item, Set Phrase, Discouse Marker Or Sentence Filler,To Continue Last Language Used (Triggering}, To Qoute Someone, To Emphasize, To Spesify Speaket Addressee, To Qualify Message: Amplify Or Emphasize, To Specify Speaker Involvement, To Mark And Emphasize Group Identity (Solidarity), To Convey Confidentially, Anger, Annoyance, To  Exclude Someone From Conversation, To Change Role Of Speaker: Rise Status, Add Authority, Show Expertise.But from the six function s of code switching  applied, there are only five functions of code switching found in the novel ; they are Referential Function, Expressive Function, Phatic Function, Metalinguistic Function And Poetic Function. And based on the reasons of code switching, there were only seven which were found in the novel”Critical Eleven” ; they are To Fill A Linguistic Need For Lexical Item, To Continue The Last Language Used (Triggering), To Quote Someone, Specify Addressee, To Specify Speaker Involvement, To Mark And Emphasize Group Identify (Solidarity) And To Convey Confidentially, Anger, And Annoyance.